Canva as a Creative Digital Learning Media for English Learning: A Student Perception Study - Fathin Amalina Savitri; Devinta Puspita Ratri (South Sulawesi Education Development (SSED), 2025)
This study investigates students’ perceptions of using Canva as a digital learning tool in English classes. The objective is to explore Canvas impact on students' motivation, interest, efficacy, challenges, and preferences. A quantitative method was employed by distributing questionnaires to 100 10th-grade students at an Islamic high school in East Java, Indonesia. The findings reveal that most students hold positive perceptions of Canva, particularly in enhancing their motivation and engagement in learning. Canvas visual and interactive features also support students' understanding and boost their confidence in learning English. Nevertheless, some challenges, such as limited technology access, were reported. These results suggest that Canva can be an effective tool for fostering student engagement and developing independent learning habits. The study highlights the importance of integrating digital tools like Canva into English instruction to create more meaningful and engaging learning experiences.